1995
DOI: 10.1039/an9952002171
|View full text |Cite
|
Sign up to set email alerts
|

Use of focused microwaves for expeditive shortening of sample pre-treatment: digestion and reduction procedures prior to selenium speciation as selenium(IV) or selenium(VI)

Abstract: Digestion programmes for different types of samples (milk, sausage and lyophilized pig kidney certified reference material) have been developed using a focused microwave digestor prior to the determination of selenium. The digestion step does not alter the oxidation state of the analyte; thus, the speciation of the target analyte is also achieved with the help of the microwave digestor, which facilitates a subsequent on-line reduction step in a flow injection (F'I) manifold before determination by FI cathodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 15 publications
0
15
1
Order By: Relevance
“…Another method which more efficiently de-aerates the closed beaker needs to be developed. This is contrary to the observations reported elsewhere [18], although it is noted that those researchers used a focussed microwave instrument, with a very different sample matrix.…”
Section: Closed Beaker Digestioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Another method which more efficiently de-aerates the closed beaker needs to be developed. This is contrary to the observations reported elsewhere [18], although it is noted that those researchers used a focussed microwave instrument, with a very different sample matrix.…”
Section: Closed Beaker Digestioncontrasting
confidence: 56%
“…Previous work [18] has shown that it is possible to produce a digest that does not undergo redox reactions utilizing a focussed microwave digester; this work studied selenium in food.…”
Section: Closed Beaker Digestionmentioning
confidence: 99%
“…For natural waters, various procedures to transform Se VI and organic Se 2II to Se IV have been proposed such as thermal or photochemical treatments but these treatments were very dependent on medium and experimental conditions and sometimes contradictory. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In the first part of this study, we optimized the experimental conditions for the determination of Se IV by flow injection hydride generation, in situ trapping onto iridium followed by ETAAS; in the second part we investigated different physicochemical treatments to transform Se VI and Se 2II -selenomethionine taken as organic model to Se IV in water or seawater samples. From our results, an experimental protocol permitting an operational differentiation of selenium species in seawater was proposed.…”
mentioning
confidence: 99%
“…In these conditions, a complete mineralisation with nitric acid alone has been reported in shellfish tissue samples 30 and different foodstuffs, [33][34][35] or with a mixture of nitric acid with H 2 O 2 in autopsy tissues, 36 human milk 37 and foodstuffs. 13,38,39 However, Lan et al 40 reported that not all microwave assisted digestion procedures, assessed in the same conditions of time and power, led to a complete destruction of some of the organic selenium compounds present in samples. Despite this, by changing various program parameters such as temperature and time the complete digestion can be achieved.…”
Section: Procedures IImentioning
confidence: 99%